The pecking order of innovation finance - Andrea Mina; Henry Lahr (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
This paper examines the relationship between firms' innovation activities and the hierarchy of financing behaviours. We analyse the role of innovation inputs (R&D), intermediate outputs (patents) and outcomes (product and process innovations) as sources of information asymmetry in financing decisions. Our focus on mainly unlisted companies allows us to study the effects of information asymmetries in the context where they are most severe, that is, among small and medium-sized firms. We identify the effect of innovation, alongside the size of the firm, its age and its human capital, on the order of directly observed external capital allocations. Our results show that innovation is strongly associated with a pecking order characterised by increasing agency costs, and that the more uncertain the innovation signal, the stronger its effect on the pecking order. In further robustness tests, this relationship and associated hierarchy of external financing emerge from the data without imposing an a-priori pecking order.
Keywords: G32; O16; O30; 330; R&D; innovation; information asymmetries; capital structure; pecking order